2008
DOI: 10.1063/1.2833432
|View full text |Cite
|
Sign up to set email alerts
|

Further characterization of oxygen vacancies and zinc vacancies in electron-irradiated ZnO

Abstract: Electron paramagnetic resonance (EPR) has been used to monitor oxygen vacancies and zinc vacancies in a ZnO crystal irradiated near room temperature with 1.5MeV electrons. Out-of-phase detection at 30K greatly enhances the EPR signals from these vacancies. Following the electron irradiation, but before illumination, Fe3+ ions and nonaxial singly ionized zinc vacancies are observed. Illumination with 325nm laser light at low temperature eliminates the Fe3+ signal while producing spectra from singly ionized oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
91
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 41 publications
23
91
1
Order By: Relevance
“…41,42,48 On the other hand, under illumination at low temperatures, ionized V Zn can be transformed to the neutral charge state. 49 Detailed investigation of V Zn properties under illumination has been studied by Evans et al 50 In this work, illumination on the ZnO crystal with 325 nm laser light at low temperature produced the electron paramagnetic resonance signal from neutral V 0 Zn and neutral centers (V À Zn , H þ ) 0 , which were not observed before illumination. The localization energy of BE calculated from the energy difference between the FX emission and the 3.33 eV transition is about 40 meV.…”
Section: Implications Of the Experimental Resultsmentioning
confidence: 99%
“…41,42,48 On the other hand, under illumination at low temperatures, ionized V Zn can be transformed to the neutral charge state. 49 Detailed investigation of V Zn properties under illumination has been studied by Evans et al 50 In this work, illumination on the ZnO crystal with 325 nm laser light at low temperature produced the electron paramagnetic resonance signal from neutral V 0 Zn and neutral centers (V À Zn , H þ ) 0 , which were not observed before illumination. The localization energy of BE calculated from the energy difference between the FX emission and the 3.33 eV transition is about 40 meV.…”
Section: Implications Of the Experimental Resultsmentioning
confidence: 99%
“…6͒ without any hyperfine feature was observed with g value of 2.0034 and a line width of 3.5 G for as synthesized unirradiated ZnO:Li powder sample at room temperature. For detection of Li acceptor center, it has been reported that light illumination is necessary 20,21 and such spectra exhibited pronounced hyperfine structure for axial trapped hole ͑g ʈ = 2.0028, g Ќ = 2.0253͒ and for nonaxial Li-O bond direction ͑g xx = 2.0223, g yy = 2.0254, g zz = 2.0040͒. Such centers have been reported to be deep acceptors producing yellow luminescence band ͑2.05 eV͒.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by experiment. By monitoring the optical threshold for ionization of the neutral V O centre, detected using electron paramagnetic resonance (EPR), Evans et al [47] estimated the [0/2+] donor level to lie ∼ 2.1 eV below the CBM. Furthermore, using optical-detected EPR measurements, Vlasenko and Watkins [48] found the [+/0] transition level to lie either 0.9 eV or 2.48 eV above the top of the valence band maximum (VBM).…”
Section: Oxygen Vacanciesmentioning
confidence: 99%